Elementary abstract algebra. - Shukla, U. (Lucknow Prakashan Kendra, 1964)
The author subscribes to the view that abstract mathematical ideas should be introduces at a fairly early stage in the mathematical education of a student.
Keywords: Mathematics- Algebra